Sosialisasi Bahaya Stunting di Desa Pucungwetan Kecamatan Sukoharjo Kabupaten Wonosobo - Khoirul Umam; Fajar Khoirudin; Rizki Mei Nur Aulana; Safika Rodiah; Dwi Khafsoturrohmah; Melina Mutiara Putri; Siti Syarofah; Khofifah Desi Romadoni; Farrah Humaida Amini; Uswatun Hasanah; Muhtar Shofwan Hidayat (Jurnal Pengabdian Masyarakat Madani, 2022)
This community sevice lecture activity is carrued out thematically. One of its work programs is to provide stunting treatment in Pucungwetan village. The purpose of this study is to increase public awareness abaout the dangers of stunting and how to handle it in order to reduce the risk of dtunting children. The research method used is interview, documentation, and observation. The results of this study are increasing public awareness of the dangers of stunting and increasing knowladge abaout stunting handling. Cadres in posyandu have been educated about the dangers of tunting in order to change people’s mindsets.